WORK IN THE DIGITAL PLATFORMS IN THE CONTEXT OF HISTORICAL BACKGROUND, VARIETY OF TASKS, IMPACTS ON WORKERS, AND LEGAL FRAMEWORK (Third Sector Social Economic Review, 2024)
Digital labor platforms which has a rapid growth in last ten years have introduces alternatives to standart employment and working modeld, giving rise to academic debates on the various forms of digital work. This study addresses the historical development, variety and conceptual categorization of platform work, along with its impact on waged workers, and the legal framework of platform work. With the development of global production networks by the end of the twentieth century, digital transformation gained momentum within economy. Following the period after the great recession of the early 2000s, along with the increasing permeability of both the workplace and national borders, companies turned to creating a ready pool of labor, leading to the proliferation of crowdwork platforms. Jobs facilitated through platforms encompass a wide variet classified into specific categories based on criteria such as skill level, nature of the tasks, and wheather it can be done on location or online. Within this diversity; platforms are discussed in terms of their positive effects on workers, providing independence and flexibility, as well as their negative aspects in the context of insecurity and intense surveillance. From a legal perspective, attention is drawn to the negative consequences arising from the uncertainty of the status of workers on platforms. In conclusion, digital labor platforms offer supplement to main income, freelance opportunities, and in part, the control over the tasks and working conditions; however, they generally create insecure and unsecure work that is highly controlled by the platforms. Considering current trends towards the platformization of jobs, these points provide insights into the challenges that workers my face in the near future.
Keywords: work platforms; digital platforms; crowdwork; non-standard employment